KINERJA GURU HONORER DALAM PEMBELAJARAN DI SMP - Natanael Tri Prasetyo Adi Nugroho; Rohiat Rohiat; Puspa Djuwita (Manajer Pendididikan, 2017)
This study aims to determine how the non permanent teachers perform at SMPN 12 Ketahun of North Bengkulu. This study used descriptive qualitative and evaluative method. From the result we can conclude that the non permanent teachers at SMPN 12 Ketahun have been able to show good performance. Non permanent teachers at SMPN 12 Ketahun have a complete teaching equipments, learning program, and able to manage a class well. The results also showed that the non permanent teachers performance in assesment is already good. Eight teachers can be categorized as excellent performance since the eight non permanent teachers have been able to compile a syllabus, make lesson plans, implement the learning activites and conduct learning evaluation.